Pengaruh Pesan Kampanye #GenerasiKulitSehat terhadap Kesadaran Merek Kosmetik NPURE (Survei pada Pengikut Instagram @npureofficial) - Ajeng Purnama, Raden Hutami; Valdiani, Dini; Noegroho, Jati (KOMUNIKOLOGI: Jurnal Ilmiah Ilmu Komunikasi, 2024)
In recent years, the cosmetics and health industry in Indonesia has experienced a rapid rise. Cosmetics industry players compete so that their products can be accepted by consumers. Cosmetics industry players can build corporate identity by building strong brand awareness. NPURE held the #GenerasiKulitSehat campaign as a form of sensitivity to the problems experienced by many Indonesians, namely wanting white and smooth skin. In this research, the campaign message designed aims to increase the audience's brand awareness of NPURE products with natural ingredients and relevant issues that are experienced by many Indonesians. If the audience has an imprinted awareness of a brand and sees it as a reliable and high-quality brand, they will most likely have a positive attitude towards the brand. Based on this phenomenon, the author is interested in examining the influence of the #GenerasiKulitSehat campaign message on NPURE cosmetics brand awareness. This study aims to analyze the effect of the #GenerasiKulitSehat campaign message on NPURE cosmetics brand awareness. This research uses quantitative methods with a descriptive approach. The results showed that there was an influence between the #GenerasiKulitSehat campaign message on NPURE cosmetics brand awareness by 75.9 percent.